Glikl : Memoirs 1691-1719. - Glueckel, of Hameln, 1646-1724 (Tauber Institute for the Study of European Jewry series (Unnumbered), 2019)
These words from the memoirs Glikl bas Leib wrote in Yiddish between 1691 and 1719 shed light on the life of a devout and worldly woman. Writing initially to seek solace in the long nights of her widowhood, Glikl continued to record the joys and tribulations of her family and community in an account unique for its impressive literary talents and strong invocation of self. Through intensely personal recollections, Glikl weaves stories and traditional tales that express her thoughts and beliefs. While influenced by popular Yiddish moral literature, Glikl's frequent use of first person and the significance she assigns her own life experience set the work apart. Informed by fidelity to the original Yiddish text, this authoritative new translation is fully annotated to explicate Glikl's life and times, offering readers a rich context for appreciating this classic work.